Implementasi Kurikulum Berbasis Local Wisdom pada Pembelajaran Seni Kuliner : Studi Kasus Program Studi S1 Pendidikan Vokasional Seni Kuliner - Wiwik Gusnita; Nizwardi Jalinus; Rijal Abdullah; Ridwan (The Indonesian Journal of Computer Science, 2024)
The existence of this local wisdom-based curriculum can increase the younger generation's awareness of social and cultural identity which is currently starting to be abandoned and turned to the western world. This research aims to identify forms of local wisdom and describe in more detail the implementation of a local wisdom-based curriculum. This research method is descriptive qualitative by adding the VOSviewer application to obtain relevant data. This study refers to the application of a local wisdom-based curriculum to the FPP-UNP Culinary Arts Vocational Education Study Program. The research results show that graduates of the culinary arts vocational study program also have competence in processing randang and traditional Minangkabau food to develop entrepreneurship and support tourism in West Sumatra. The implementation of a local wisdom-based curriculum in the Culinary Arts Vocational Education undergraduate study program adapts to three national higher education standards, namely content standards, process standards and assessment standards.